Myelofibrosis – A less known complication of vitamin D deficiency: A case report with review of literature - Ruchi Mishra; Mukesh Agrawal; Omkar Gajanan Nalavade; Darshan G Hegde (Indian Pediatrics Case Reports, 2023)
Background: Pediatric myelofibrosis is uncommon and is usually secondary to an underlying hematopoietic or nonhematopoietic condition. Among the nonhematopoietic secondary causes, Vitamin D deficiency is an important but rare cause. Clinical Description: An 18-month-old male child with delay in achieving milestones for the past 6 months along with anemia and distention of the abdomen for the past 3 months was referred to our institute. Clinical examination revealed global developmental delay with a developmental quotient of 49%, short stature, rachitic features, and massive splenomegaly. Management and Outcome: After ruling out common nutritional and hemolytic causes of anemia, a bone marrow biopsy was done which showed extensive fibrosis, few megakaryocytes, myeloid and erythroid cells with normal maturation, and no storage cells – features consistent with myelofibrosis possibly secondary to Vitamin D deficiency. The clinical and laboratory findings of myelofibrosis improved with Vitamin D therapy and calcium. Conclusion: In developing countries like India, nutritional rickets is highly prevalent. However, rarely such children with rickets may show anemia with extramedullary erythropoiesis. If pediatricians are aware of Vitamin D deficiency-induced secondary myelofibrosis, many unnecessary investigations and work-up for storage diseases can be avoided. The condition is easily reversible with Vitamin D therapy.